Is there difference in democracy promotion? A comparison of German and US democracy assistance in transitional Tunisia. Issue 7 (3rd October 2019) - Holthaus, Leonie
ABSTRACT: Since the 1990s, comparative scholars and constructivists have recognized the universally liberal character of democracy promotion and yet continued the analysis of difference in this area. Mainly in studies of German and US democracy promotion, constructivists have demonstrated the recurring and difference-generating impact of ideational factors. In this article, I hence assume the likeliness of difference and address the question of how we can analyse and explain those differences through a comparison of German and US democracy assistance in transitional Tunisia. I conceive of Germany and the US as a dissimilar pair and adopt a broad perspective to uncover differences at the diplomatic level and between and within the respective approaches to democracy assistance in Tunisia. Theoretically, I argue that national role conceptions hardly impact democracy assistance in a clear manner, and that roles are renegotiated in the process. I rather focus on liberal and reform liberal conceptions of democracy, which shape perceptions of the local context, and democracy assistance agencies different organizational cultures, which impact civil society support. Finally, I account for transnational dialogue and coordination as a factor mitigating differences in democracy promotion.